2020
DOI: 10.5194/bg-17-3247-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for non-turbulent methane escape from the East Siberian Arctic Shelf

Abstract: Abstract. The East Siberian Arctic Shelf (ESAS) hosts large yet poorly quantified reservoirs of subsea permafrost and associated gas hydrates. It has been suggested that the global-warming induced thawing and dissociation of these reservoirs is currently releasing methane (CH4) to the shallow coastal ocean and ultimately the atmosphere. However, a major unknown in assessing the contribution of this CH4 flux to the global CH4 cycle and its climate feedbacks is the fate of CH4 as it migrates towards the sediment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 144 publications
0
25
0
Order By: Relevance
“…An extrapolation based on an arithmetic was chosen because there was no significant relationship between water depth or sediment type and benthic flux. Although 3D kriging methods have been used to derive shelf-wide sedimentation rates for the Siberian shelf sea based on a few 210 Pb-based sedimentation rates (Puglini et al, 2020), an analysis of 313 records of surface sediment organic carbon contents and δ 13 COC values from the Circum-Arctic Sediment Carbon Database (Martens et al 2020) revealed no systematic variations for these two seas as a function of water depth. The OC contents of the stations studied here ranged between 0.37 and 1.7% with δ 13 COC values varying from -25.8 to -22.3‰ and were well within the range of 0.2 -1.5% for OC and -26 --23 ‰ for δ 13 COC values in surface sediments in the CASCADE database.…”
Section: The Role Of Benthic Fluxes For Water Column Nutrient Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extrapolation based on an arithmetic was chosen because there was no significant relationship between water depth or sediment type and benthic flux. Although 3D kriging methods have been used to derive shelf-wide sedimentation rates for the Siberian shelf sea based on a few 210 Pb-based sedimentation rates (Puglini et al, 2020), an analysis of 313 records of surface sediment organic carbon contents and δ 13 COC values from the Circum-Arctic Sediment Carbon Database (Martens et al 2020) revealed no systematic variations for these two seas as a function of water depth. The OC contents of the stations studied here ranged between 0.37 and 1.7% with δ 13 COC values varying from -25.8 to -22.3‰ and were well within the range of 0.2 -1.5% for OC and -26 --23 ‰ for δ 13 COC values in surface sediments in the CASCADE database.…”
Section: The Role Of Benthic Fluxes For Water Column Nutrient Budgetsmentioning
confidence: 99%
“…Reaction rates and sediment-bottom water fluxes were calculated from the concentration profiles of DSi, NH 4 , DIP, and total dissolved iron (DFe) in accordance with the general steady state reaction-transport equation described in Brüchert et al (2018). This model is excellent at determining the benthic flux by determining a steady state depth concentration profile of a modeled chemical compound without engaging a full set of sediment physical and biogeochemical parameters that are necessary for fully coupled diagenetic reaction transport models (e.g., Arndt et al, 2013;Berg et al, 2003;Puglini et al, 2020). Here the benthic flux is calculated from the mass balance between production and consumption due to dissolution, precipitation, reduction, and oxidation reactions relative to transport by molecular diffusion, bioturbation, and advection (Berg et al, 1998).…”
Section: Benthic Flux Calculationsmentioning
confidence: 99%
“…Dale et al, 2008a;Jørgensen et al, 2019a;Knab et al, 2008;Mogollón et al, 2012;Oni et al, 2015aOni et al, , 2015b to hundreds of meters (e.g. Arndt et al, 2009;Wehrmann et al, 2013) as a function of different environmental controls such as, among others, OM quantity and quality, sedimentation rate, active fluid flow, or microbial growth dynamics (Puglini et al, 2020;Regnier et al, 2011). Reflecting the diversity of the depositional environments studied here, we observe a broad range of SMTZ depths (Fig.…”
Section: Anaerobic Oxidation Of Methane Dynamicsmentioning
confidence: 79%
“…Marine sediments represent the largest pool of methane in the global carbon cycle. However, up to 90% of 4 produced in marine sediments is anaerobically oxidised via sulfate reduction (Jørgensen et al, 2019b;Puglini et al, 2020;Regnier et al, 2011). AOM not only represents an efficient benthic 4 sink, it also exerts an important influence on the balance between organoclastic sulfate reduction and methanogenesis (Jørgensen et al, 2019b;Jørgensen and Kasten, 2006) and has important implications for benthic alkalinity fluxes (e.g.…”
Section: Anaerobic Oxidation Of Methane Dynamicsmentioning
confidence: 99%
“…While previous work has demonstrated that the low CH4 fluxes to the atmosphere from seaps and GHs is due to the capacity of methanotrophic bacteria to rapidly convert CH4 to CO2 in the water column e.g. (Silyakova et al, 2020), (Puglini et al, 2020) demonstrated that 'sudden' sea floor CH4 releases yield a 'window of opportunity' for emissions before microbial communities can react to changing water column CH4.…”
Section: Arctic Changementioning
confidence: 99%